From the Moon to Pluto: the Use of Impact and Convection Modeling as a Window Into Planetary Interiors - Alexander J Trowbridge (2020)
Planetary science is often limited to only surface observations of planets requiring the development of modeling techniques to infer information about the planet’s interior. This work outlines three separate scientific problems that arose from planetary surface observations, the methodology utilized to explain the formation of these observation, and what we learned about the planet’s interior by solving these problems. Chapter 1 discusses why lunar mascon basins (impact basins associated with a central freeair gravity positive) form for only a limited range of basin diameters. Modeling the full formation of South-Pole Aitken (SPA) basin using a sequential two-code (hydrocode and Finite Element Model) shows that due to SPA’s great size (long wavelength) and the high geothermal gradient of the Moon at impact, the basin’s relaxation process was controlled by isostatic adjustment with minimal influence from lithospheric rigidity or membrane stresses. Additionally, the modeling shows that the Moon was hot and weak at impact. Chapter 2 addresses why there is a lack of olivine abundance on Mars around large impact basins, and the formation of the megabreccia that is associated with an orthopyroxene signature in the circum-Isidis Planitia region. Hydrocode modeling of the excavation of the Isidis forming impact shows the impact was more than capable of excavating mantle material and reproducing the observed megabreccia. This coupled with the lack of olivine signature indicates that the Martian upper mantle is orthopyroxene-rich. Chapter 3 covers the investigation into why the nitrogen ice sheet on Pluto, Sputnik Planitia, is the youngest observed terrain and why the surface is divided into irregular polygons about 20– 30 kilometers in diameter. The utilization of a new parameterized convection model enables the computation of the Rayleigh number of the nitrogen ice and shows that the nitrogen ice is vigorously convecting, making Rayleigh–Bénard convection the most likely explanation for these polygons (Trowbridge et ...